ROLE OF TOPICAL NEPAFENAC IN PREVENTING INCREASE IN MACULAR THICKNESS AFTER PHACOEMULSIFICATION - Ullah, Wali; Irfan, Muhammad; Khan, Shahid Abdur Rauf; Ghalib, Adnan; Khalil, Zia Uddin (Journal of Postgraduate Medical Institute, 2021)
Objective: To compare mean increase in macular thickness in patients using topical Nepafenac and standard treatment with standard treatment alone, after phacoemulsifation. Methodology: This was a comparative cross sectional study which involved 84 patients operated for age related cataract. Pre-operative ocular coherence tomography was performed to document the central macular thickness and patients were randomly allocated to 2 groups. Group A received topical Nepafenac 0.1% in addition to the standard post-operative topical medication. Group B received only standard regimen of topical medications including antibiotics and steroids. Phacoemulsification was performed in both groups. Post-operative OCT was done to measure central macular thickness after 2 months of surgery. Mean increase in central macular thickness was compared between the two groups. Results: Out of 84 patients, males were 45 (53.57%) and females were 39 (46.42%). Male to female ratio was 1: 1.15. Average age was 58.65 years + 6.01 SD. The mean pre-operative macular thickness was 234.4 um + 1.72 SD while the mean post-operative macular thickness was 240.07 um + 11.43 SD. The mean increase in macular thickness was 6.85um + 4.69SD. Group A (Nepafenac group) showed significantly lesser increase in macular thickness after cataract surgery as compared to Group B (Non- Nepafenac group). Conclusion: Topical Nepafenac is associated with less mean increase in macular thickness after cataract surgery. It has a prophylactic role and reduces the occurrence of post-operative macular edema.